High density ERP indices of conscious and unconscious semantic priming. - Ruz, M; Madrid, E; Lupiáñez, J; Tudela, P (2003)
The existence of differential brain mechanisms of conscious and unconscious processing is a matter of debate nowadays. The present experiment explores whether conscious and unconscious semantic priming in a lexical decision task at a long prime-target stimulus onset asynchrony (SOA) correlate with overlapping or different event related potential (ERP) effects. Results show that the N400 effect, which appeared when words were consciously perceived, completely disappeared when primes were masked at a level where the ability of participants to detect the prime was near chance. Instead, a rather different set of ERP effects was found to index unconscious semantic priming. This suggests that the processes at the basis of conscious and unconscious semantic analyses can under some circumstances be rather different. Moreover, our results support the notion that conscious and unconscious processes are at least partially separable in the brain.